miR-425-5p targets TGF-β1/Smad2 signaling pathway to attenuate collagen fiber deposition in hypertrophic scar tissue in mice - LIANG Yan, WANG Lijuan, WU Huilin (Jichu yixue yu linchuang, 2023)
Objective To investigate the role and mechanism of miR-425-5p in the formation of hypertrophic scar(HS).Methods The levels of miR-425-5p, transforming growth factor-β1 (TGF-β1) and SMAD family member 2 (Smad2) in 16 pairs of HS tissue and normal skin tissue were detected by RT-qPCR and Western blot. The fibroblast cells were divided into nine groups: control group, miR-425-5p-mimic group, NC-mimic group, miR-425-5p-inhibitor group, NC-inhibitor group, TGF-β1-pcDNA3.1 group, NC-pcDNA3.1 group, miR-425-5p-mimic+NC-pcDNA3.1 group and miR-425-5p-mimic+TGF-β1-pcDNA3.1 group. The cells were transfected with Lipofectamine 2000. The targeting relationship between miR-425-5p and TGF-β1 was verified by dual-luciferase reporter gene assay. Hypertrophic scars in mice were induced by bleomycin(BLM), and then the mice were randomly divided into 3 groups, control group (NC-agomir), model group (NC-agomir+BLM) and intervention model group transfected with miR-425-5p (miR-425-5p-agomir+BLM), mice were treated for 21 days. Collagen fiber deposition in HS tissue was detected by Masson's trichrome staining. The expressions of miR-425-5p, type Ⅰ collagen (Col-Ⅰ), type Ⅲ collagen (Col-Ⅲ), α-smooth muscle actin (α-SMA), TGF-β1 and Smad2 in tissues and cells were detected by RT-qPCR and Western blot. Results Compared with normal group, the expression of miR-425-5p in HS group was decreased (t=4.242, P＜0.001), while the mRNA and protein expression of TGF-β1 was increased(P＜0.001). Compared with control group, the mRNA and protein expression of Col-Ⅰ, Col-Ⅲ, α-SMA, TGF-β1 and Smad2 in miR-425-5p-mimic group were all decreased (P＜0.05). Compared with control group, mRNA and protein expression of Col-Ⅰ, Col-Ⅲ, α-SMA, TGF-β1 and Smad2 in miR-425-5p-inhibitor group was all increased(P＜0.05). After co-transfection with miR-425-5p-mimic, the relative luciferase activity of TGF-β1-3′-UTR-WT group was reduced as compared with TGF-β1-3′-UTR-MUT group (P＜0.05). Compared with miR-425-5p-mimic+NC-pcDNA3.1 group, mRNA and protein expression of Col-Ⅰ, Col-Ⅲ, α-SMA, TGF-β1 and Smad2 in miR-425-5p-mimic+TGF-β1-pcDNA3.1 group were all increased (P＜0.05). Compared with NC-agomir+BLM group, the relative collagen content of miR-425-5p-agomir+BLM group was decreased (P＜0.05) and the expression of miR-425-5p was increased (P＜0.05). The TGF-β1 mRNA and protein were decreased (P＜0.05).Conclusions The miR-425-5p is down-regulated in HS tissue, and up-regulated miR-425-5p inhibits collagen deposition and HS formation by inhibiting TGF-β1/Smad2 signaling pathway.